Pemulihan Martabat Manusia dalam Perspektif Metafisika Persahabatan - Yohanes Alfrid Aliano; F.X. Eko Armada Riyanto (Jurnal Filsafat Indonesia, 2022)
Human dignity is a special and natural value in the discourse of metaphysical philosophy. The focus of this article is intended to reveal an aspect of the natural values, namely my relationship with God, others, and nature. There is an intimate relationship in the human life that becomes a kind of "metaphysical friendship" that needs to be explore. This metaphysical friendship implies my relationship with God, other, and nature. The purpose of this research is that every human being has a spirituality of respect for the dignity of himself and his fellow human beings. Humans need to realize that they do not live alone but with God, others, and nature. The fruit of the spirituality of friendship is like a "crumb of bread" which leads to the unity of life in the principle of the "banquet table," namely Bonum Commune. Regarding methodology, we use library research through the study of various sources, books and metaphysical-philosophical articles that are in accordance with this discourse. This study finds that the friendly relationship of love with God, others, and nature is a natural unity that expresses a sublime dignity that will never be complete, final, and definitive to be translated into everyday life. The novelty in this "metaphysical friendship" is that I as "being" are in the awareness of being with others. This “awareness of being together with” is important and crucial to continue to strive for as a man of faith and reason.